RISK MANAGEMENT SYSTEM FOR SMALL AND MEDIUM-SIZED INDUSTRIAL ENTERPRISES IN WARTIME CONDITIONS - Nechayeva, Iryna; Pankova, Alla (European Science, 2024)
In the study dedicated to risk management in industrial enterprises of small and medium-sized businesses, the complexity and multifaceted nature of the concept of "risk" are emphasized. The work analyzes the essence of risks, their classification, and th